Metabolomic Strategies for Aquaculture Research: A Primer - Young, T; Alfaro, AC (Wiley-Blackwell, 2016)
Metabolomics is a fast-evolving field that provides qualitative and quantitative analyses of metabolites within cells, tissues or biofluids. Recent applications of metabolomics approaches in aquaculture research have highlighted the huge potential for solving problems within all aspects of the production line, from hatchery production to post-harvest quality control. To assist with the growing application of metabolomics in aquaculture research, this contribution provides a review of techniques and steps necessary to conduct metabolomics research, from experimental design to data interpretation. Specifically, we target scientists who are new to the field of metabolomics, and we offer simple, but comprehensive steps and strategies to conduct this type of research. We conclude this primer with some advice on how to access relevant expertise and facilities for metabolomics-based aquaculture research.
Keywords: Aquaculture; Biomarkers; Marine; Metabolomics; Omics